2018
DOI: 10.1016/j.neuropsychologia.2018.04.025
|View full text |Cite
|
Sign up to set email alerts
|

EEG alpha activity during imagining creative moves in soccer decision-making situations

Abstract: This study investigated task-related changes of EEG alpha power while participants were imagining creative moves in soccer decision-making situations. After presenting brief video clips of a soccer scene, participants had to imagine themselves as the acting player and to think either of a creative/original or an obvious/conventional move (control condition) that might lead to a goal. Performance of the soccer task generally elicited comparatively strong alpha power decreases at parietal and occipital sites, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 39 publications
5
44
1
4
Order By: Relevance
“…Higher creative potential was associated with stronger activation differences between both conditions in the left middle temporal gyrus and in the left postcentral gyrus, that is the higher the creative potential of the participants the higher is the activation of the control relative to the creative condition (or the lower the activation of the creative condition relative to control, respectively). This finding adds further evidence to the common view of domain‐specificity of creativity and nicely complements the result pattern found in the related EEG study by Fink et al (). This study revealed that the creative potential of the individuals was globally positively associated with alpha power at all cortical sites, while the soccer‐specific creativity score was associated with rather specific effects at motor related sites.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Higher creative potential was associated with stronger activation differences between both conditions in the left middle temporal gyrus and in the left postcentral gyrus, that is the higher the creative potential of the participants the higher is the activation of the control relative to the creative condition (or the lower the activation of the creative condition relative to control, respectively). This finding adds further evidence to the common view of domain‐specificity of creativity and nicely complements the result pattern found in the related EEG study by Fink et al (). This study revealed that the creative potential of the individuals was globally positively associated with alpha power at all cortical sites, while the soccer‐specific creativity score was associated with rather specific effects at motor related sites.…”
Section: Discussionsupporting
confidence: 89%
“…A similar finding has been observed during musical improvisation in jazz pianists (Limb & Braun, ). Likewise, this study suggested that with increasing creative soccer task performance the processing of sensorimotor and somatosensory information becomes increasingly important—quite similar to the result pattern obtained in the related EEG study (Fink et al, ), which revealed that more creative soccer task was associated with activation at motor related cortical sites.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations